Daya Pragmatik Tindak Tutur Ekspresif dalam Film Budi Pekerti Karya Wregas Bhanuteja - Siti Fara Dibah; Wini Tarmini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is motivated by the researcher's desire to know the expressive illocutionary speech acts in the movie Budi Pekerti. This paper aims to identify the types of expressive illocutionary speech acts spoken by the characters in the movie